Emulsifier for emulsifying SBS modified asphalt and application thereof
By forming a conjugated system with SBS modified asphalt and stone with a specific molecular structure, the problem of large amount and poor stability of SBS modified asphalt emulsifier is solved, and emulsified asphalt with low freezing point and high stability is achieved, reducing energy costs and safety risks, and improves the wear resistance and waterproof performance of the road.
Patent Information
- Application Number
- CN202411682113.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-07
AI Technical Summary
The large amount of SBS modified asphalt emulsifier is used and the freezing point is high, resulting in poor stability of emulsified asphalt and high solvent volatility and flammability, which increases transportation and storage costs and safety risks.
Using emulsifiers with specific molecular structure, containing 83% of 3 double bond unsaturated alkyl groups and 4% of 2 double bond unsaturated alkyl groups, the conjugated system is formed with SBS polymer and asphalt through Diels-Alder reaction, reducing the Freezing point, reduce the amount of emulsifier and improve stability.
It achieves a low freezing point of emulsified asphalt, improves stability, reduces energy costs and safety risks, enhances the adhesion between emulsified asphalt and stone, and extends the service life of the road.
Smart Images

Figure CN119264467A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of asphalt emulsifiers, and particularly relates to the technical field of emulsifiers used for SBS modified asphalt emulsification. Background Art
[0002] As a byproduct of petroleum refining, asphalt has good waterproof and anti-corrosion properties and excellent adhesion to various road materials and building materials such as stone and cement. It is widely used in highway construction and maintenance, waterproof membranes and waterproof coatings in buildings, heavy-duty anti-corrosion in ships, oil fields, chemical industries, etc. Due to the high freezing point of asphalt, it is usually heated to 140°C during use. o C or so to become a flowing liquid before use. When asphalt is heated, the following problems will occur: 1. The heating and insulation process will consume energy; 2. Harmful substances in the asphalt such as benzene and toluene will overflow after heating, endangering the environment and human health; 3. The high temperature use of asphalt will also cause potential harm to the operators.
[0003] SBS modified asphalt is a network structure formed by cross-linking reaction between asphalt and SBS polymer chain segments under high temperature (usually 140-150℃) and strong shearing. It has the characteristics of large molecules and easy film formation. In practical applications, it has the advantages of high softening point, good adhesion and adhesion to aggregates, resistance to solar oxidation, and resistance to low temperature cracking.
[0004] Asphalt emulsifier is the key technology that determines the processing performance, application performance and product quality of emulsified asphalt. For a long time, people have done a lot of work in the application performance of emulsified asphalt and emulsifier formula development technology, and have made relatively good progress. However, SBS modified asphalt is very difficult to emulsify due to its cross-linked macromolecular network structure.
[0005] Patent No. CN 101845228 B discloses the composition, preparation method and application of a cationic asphalt emulsifier, which can emulsify SBS modified asphalt. However, the amount of emulsifier used is large (the amount of emulsifier used is 0.5%-1% of the mass of the emulsified asphalt, which is 0.92-1.47% of the mass of the SBS modified asphalt), and the emulsification temperature of the SBS modified asphalt is high (165°C-170°C), and the one-day stability is 0.1%-0.8%. In addition, the cationic asphalt emulsifier in CN 101845228 B contains 20-55% of small molecule alcohol (such as isopropanol) as a solvent, which makes the emulsifier highly volatile and has a low flash point. It is treated as a flammable chemical during storage and transportation, which increases transportation and storage costs and increases the risk of product safety.
[0006] Patent number CN201811593163.X is a liquid fast-cracking cationic polymer emulsifier for SBS modified asphalt emulsification, the dosage of which is 0.105-1.00% of the mass of the emulsified asphalt, and 0.15-2.5% of the mass of the SBS modified asphalt. The emulsification temperature of SBS modified asphalt is 140-150°C, and it is solvent-free, but the freezing point is slightly higher, at 19-22°C. The 1-day stability is 0.1%-0.6%, and the 5-day stability is 0.3%-3.4%, that is, there are technical problems such as a slightly high freezing point and slightly poor stability. Summary of the invention
[0007] The purpose of the present application is to provide an emulsifier for SBS modified asphalt emulsification and its application in order to solve the above-mentioned technical problems such as large amount of emulsifier used, slightly high freezing point and slightly poor stability of the emulsified asphalt during emulsification of SBS modified asphalt.
[0008] Technical principle of this application
[0009] Petroleum asphalt itself contains more than 80% aromatic rings, in addition to carbon, hydrogen and oxygen elements, it also contains sulfur and nitrogen heteroatoms (Production and Application of Petroleum Asphalt, edited by Zhang Deqin, China Petrochemical Press, 2001). SBS polymer is obtained by copolymerization of styrene monomer and butadiene monomer, which also contains a large number of double bonds and benzene rings. When there are multiple double bonds in the lipophilic part of the emulsifier, it is easier to react with the double bonds in the SBS polymer molecules and the aromatic rings in the asphalt. That is, the conjugated system can undergo a conjugated addition reaction (for details, see Advanced Organic Chemistry (Fourth Edition) Volume 2, edited by Hu Hongwen, Higher Education Press, published in 2013, Chapter 29 Pericyclic Reaction). The emulsifier, SBS modified polymer and asphalt form a unified whole due to chemical reaction, thereby ensuring that the final SBS modified asphalt emulsion has good stability, and asphalt and SBS modifier will not separate from the modified asphalt emulsion to cause demulsification.
[0010] The technical solution of this application
[0011] An emulsifier for SBS modified asphalt emulsification, its molecular structure is as follows: ; The R1 described in the above molecular structure is composed of mixed octadecanoic unsaturated alkyl groups containing 1 double bond, 2 double bonds and 3 double bonds and saturated alkyl groups containing 16 and 18 carbon atoms. The composition and content thereof are as follows, calculated by the mass percentage of carbon atoms: Octadecanunsaturated alkyl containing 1 double bond 8% 4% octadecanoic unsaturated alkyl containing 2 double bonds Octadecanunsaturated alkyl containing 3 double bonds 83% Saturated alkyl containing 16 carbon atoms 4% 1% saturated alkyl containing 18 carbon atoms; The double bond position of the octadecanoic unsaturated alkyl group containing one double bond is between carbon atoms 9-10; The double bond positions of the octadecanoic unsaturated alkyl group containing two double bonds are respectively between the 9th-10th and 12th-13th carbon atoms; The octadecanoic alkyl group containing three double bonds is composed of an octadecanoic alkyl group whose double bond positions are between the 9th to 10th, 12th to 13th, and 15th to 16th carbon atoms and an octadecanoic alkyl group whose double bond positions are between the 9th to 10th, 11th to 12th, and 13th to 14th carbon atoms, respectively. The mass ratio of the octadecanoic alkyl group whose double bond positions are between the 9th to 10th, 12th to 13th, and 15th to 16th carbon atoms to the unsaturated alkyl group whose double bond positions are between the 9th to 10th, 11th to 12th, and 13th to 14th carbon atoms is 3:80. The above X is O or NH; M is N or NH; R2 is a straight chain C3H6; R3 is a branched C 3-9 H 7-19 O 1-3 ; R4 is hydrogen or branched C 3-6 H 7-13 O 1-2 ; The above R3 and R4 are the same or different.
[0012] Preferably, in the molecular structure formula: The M is N; Branched chain C 3-9 H 7-19 O 1-3 For branched chain C9H 19 O3, branched C3H7O or branched C6H 13 O2; Branched chain C 3-6 H 7-13 O 1-2 It is branched C3H7O or branched C6H 13 O2.
[0013] More preferably, in the molecular structure: The X is O, M is N, and R3 is a branched C9H 19 O 3、 R4 is a branched C6H 13 O2.
[0014] More preferably, in the molecular structure: X is NH, M is N, and R3 is a branched C6H13 O2 and R4 are hydrogen.
[0015] More preferably, in the molecular structure: X is NH, M is N, R3 is branched C3H7O, and R4 is branched C3H7O.
[0016] The above-mentioned emulsifier for SBS modified asphalt emulsification is used in SBS modified asphalt emulsification. The amount of the emulsifier for SBS modified asphalt emulsification and SBS modified asphalt used for emulsification is 0.5:100 according to the mass ratio of the emulsifier for SBS modified asphalt emulsification: SBS modified asphalt. The temperature is controlled at 140-150°C during the emulsification process.
[0017] In the emulsified asphalt obtained above, the mass ratio of the emulsifier used for emulsification of SBS modified asphalt: emulsified asphalt is 0.3:100.
[0018] The application method of the above-mentioned emulsifier for SBS modified asphalt emulsification in SBS modified asphalt emulsification refers to patent CN201811593163.X.
[0019] The above-mentioned application of the emulsified asphalt in road maintenance or new road construction is specifically carried out in accordance with the industry standard JTG / TF40-02-2005.
[0020] Beneficial technical effects of this application
[0021] The emulsifier for SBS modified asphalt emulsification of the present application has a low freezing point of 15-17°C, so it is a transparent liquid at room temperature and can be used at a relatively low temperature. Since it is a liquid at room temperature, it is convenient to use and does not need to be heated to melt into a liquid when used. At the same time, since it is solvent-free, the emulsifier used for SBS modified asphalt emulsification directly participates in the emulsification, so when it is used for the emulsification of SBS modified asphalt, its usage is relatively reduced, and the usage is only 0.5% of the mass of SBS modified asphalt calculated based on SBS modified asphalt, thereby reducing the raw material cost of SBS modified asphalt emulsification.
[0022] Furthermore, in the emulsifier for emulsification of SBS modified asphalt of the present application, since the unsaturated alkyl part of the lipophilic group R1 mainly contains 3 double bonds, the mass percentage content of carbon atoms of the unsaturated alkyl groups with 3 double bonds is as high as 83%, the mass percentage content of carbon atoms of the unsaturated alkyl groups with 2 double bonds is 4%, the mass percentage content of carbon atoms of the unsaturated alkyl groups with 1 double bond is 8%, and the total carbon atoms of the saturated alkyl groups (16C+18C) is only 5%. It is precisely this emulsifier with a special structure that, when adsorbed on the interface of SBS modified asphalt and mixed stone, the attraction between multiple double bonds is greater than that between saturated CC bonds, so that the emulsifier for emulsification of SBS modified asphalt of the present application forms a better bonding film between SBS modified asphalt and stone. Therefore, the emulsified asphalt prepared using this emulsifier for emulsification of SBS modified asphalt has stronger adhesion to the stone surface.
[0023] Furthermore, when SBS modified asphalt is emulsified using the emulsifier for SBS modified asphalt emulsification of the present application, the prepared emulsified asphalt has a small average particle size, uniform distribution, and high stability. It also shows that when the emulsified asphalt is mixed with the aggregate, it can be evenly wrapped on the surface of the aggregate and has strong adhesion to the aggregate. The adhesion between the obtained emulsified asphalt and the aggregate is tested to be 100%.
[0024] Furthermore, since the emulsifier used for SBS modified asphalt emulsification of the present application has multiple unsaturated double bonds on the molecular hydrophobic group chain, in the emulsified asphalt dispersion prepared by using this emulsifier for SBS modified asphalt emulsification, the monomolecular film of the emulsifier molecules on the surface of the dispersed asphalt particles has a strong density, and the enrichment density of the emulsifier molecules used for SBS modified asphalt emulsification on the surface of the SBS modified asphalt particles is large, and the dispersibility of the SBS modified asphalt particles will be better. Therefore, the emulsifier used for SBS modified asphalt emulsification has good emulsification performance for SBS modified asphalt, and can emulsify SBS modified asphalt well, so that the final SBS modified asphalt emulsion has good stability, and the SBS modified asphalt and the emulsifier will not separate from the emulsified asphalt liquid to cause demulsification. After testing, the emulsified asphalt obtained by emulsifying SBS modified asphalt with the emulsifier used for emulsification of SBS modified asphalt in the present application has a sieve residue of 0, no SBS modified asphalt is separated out, and the 1-day stability of the emulsified asphalt is tested to be 0, and the 5-day stability is 0.1%-0.2%.
[0025] Furthermore, the emulsifier for SBS modified asphalt emulsification of the present application has a relatively low emulsification temperature of only 140-150° C. when used for the emulsification of SBS modified asphalt, thereby reducing the energy cost of the SBS modified asphalt emulsification.
[0026] Furthermore, when preparing emulsified asphalt, the emulsifier for SBS modified asphalt emulsification of the present application does not contain any organic solvent. Therefore, when the emulsifier is used for preparing emulsified asphalt, the preparation process is environmentally friendly and complies with the concept of environmentally friendly production.
[0027] Furthermore, after emulsifying SBS modified asphalt using an emulsifier for SBS modified asphalt emulsification of the present application, the resulting emulsified asphalt has better waterproof and anti-stripping properties in actual road maintenance and new road construction, can extend the service life of the road and withstand extreme high temperature and high humidity climates. DETAILED DESCRIPTION
[0028] The present invention is further described below by means of specific examples, but the present invention is not limited thereto.
[0029] The equipment used in each embodiment of the present application: colloid mill (DM-005V, Dawes), production capacity 100-300 liters of asphalt emulsion / hour, voltage: 380 / 220VAC, current: 3.4 / 5.9A, speed: 2870R / M, motor power: 1.5KW; The specifications and manufacturer information of the raw materials used in each example of this application are as follows: Aqueous hydrochloric acid solution with a mass percentage concentration of 28%, industrial grade, produced by Taixing Jinghe Chemical Plant; SBS modified asphalt Ssangyong 70#, produced by Ssangyong Company of South Korea; The emulsifiers used for emulsification of SBS modified asphalt described in Examples 1, 2, and 3 are all industrial grade and are exclusively produced by Zhangjiagang Feixiang Chemical Co., Ltd. on behalf of Qinong Chemical Technology (Shanghai) Co., Ltd.; The application of an emulsifier for SBS modified asphalt emulsification in the preparation of emulsified asphalt specifically comprises the following steps: (1) Calculated by mass percentage, the ratio of deionized water: 28% hydrochloric acid aqueous solution by volume: emulsifier for emulsification of SBS modified asphalt: SBS modified asphalt is 39.4%: 0.3%: 0.3%: 60%. Prepare 394 g of deionized water, 3 g of 28% hydrochloric acid aqueous solution by volume, 3 g of emulsifier for emulsification of SBS modified asphalt and 600 g of SBS modified asphalt; (2) Heat 394 g of deionized water to 55° C., add 3 g of a 28% by volume hydrochloric acid aqueous solution, control the speed to 80-100 r / min, and add 3 g of an emulsifier for emulsification of SBS modified asphalt at a rate of 5 g / min. Continue stirring after the addition is completed until a transparent homogeneous solution, i.e., a soap solution, is formed. The temperature is controlled to 50-60° C. and kept warm for later use; (3) Liquid asphalt preparation Control the temperature to 140-150°C to heat 600g of SBS modified asphalt until it becomes a flowing liquid with a viscosity of 10-1000cp (the instrument used for viscosity testing is RS75 rheometer, manufactured by HAAKE Company, and the test method is carried out according to the instruction manual of the tester) to obtain liquid asphalt, and continue to control the temperature to 140-150°C to keep it warm for standby use; The SBS modified asphalt is Shuanglong 70# SBS modified asphalt; (4) Preheating of colloid mill Rinse the colloid mill with 2L of 80-90℃ hot water and make the grinding head temperature reach 60-90℃, control the speed of the colloid mill to 2800-2900r / min, release all the hot water, and close the colloid mill and the outlet valve; (5) Add the soap solution obtained in step (2) to the preheated colloid mill at a rate of 800 g / min. After adding, start the colloid mill and control the rotation speed of the colloid mill to 2800-2900 r / min. Add the liquid asphalt obtained in step (3) to the soap solution in the colloid mill at a rate of 300 g / min. After adding, continue grinding for 1 min to obtain emulsified asphalt. Open the discharge valve to release the emulsified asphalt.
[0030] The method for determining the freezing point of the emulsifier used for SBS modified asphalt emulsification in each embodiment of the present application and the emulsifier of the prior art used in the application control example is as follows: According to GB9104.5-88, about 30g of the emulsifier sample is melted to a temperature at least 10°C higher than the freezing point. Place it in a freezing tube to the scale, insert a thermometer and a stirrer, and place the mercury ball of the thermometer at about 45mm below the scale. When the sample begins to solidify, measure the highest temperature reached during solidification.
[0031] The 1-day and 5-day stability test method of the emulsified asphalt obtained in each application example and application control example of the present application is as follows: the storage stability test of the emulsified asphalt is carried out in accordance with T-0655-1993. That is, about 250 ml of emulsified asphalt is placed in the measuring cylinder described in T-0655-1993, and left to stand at room temperature (about 25°C) for 24 hours to measure the 1-day stability, and left to stand for 5 days to measure the 5-day stability. Take 50 g of emulsion from the upper and lower parts of the measuring cylinder respectively, and measure the evaporation residual percentage. The difference between the evaporation residual percentage of the upper and lower parts is the emulsion stability, and the smaller the difference, the better the stability.
[0032] The test method for the adhesion of emulsified asphalt to aggregates is in accordance with T0621-1993. Soak 10-20 limestones with a size of 10-15 mm in water for 1 minute, take them out and immediately soak them in emulsified asphalt for 1 minute, take out the crushed stones and place them on a 14-mesh sieve (1.4 mm), let them stand at room temperature (about 25°C) for 5 hours, then soak these crushed stones in 80°C hot water for 1 hour, observe the peeling of asphalt, visually observe the proportion of the surface area of these crushed stones covered by asphalt, and calculate the adhesion area. The larger the area covered by asphalt, the stronger the adhesion between the emulsified asphalt and the aggregate; The emulsification performance test of the emulsifier used for SBS modified asphalt emulsification is in accordance with T0652-1993. The emulsification performance of the emulsifier on asphalt is measured by the amount of residue on the sieve. The lower the residue on the sieve, the better the emulsification performance. Example 1
[0033] An emulsifier for SBS modified asphalt emulsification, its molecular structure is as follows: ; The R1 described in the above molecular structure is composed of mixed octadecanoic unsaturated alkyl groups containing 1 double bond, 2 double bonds and 3 double bonds and saturated alkyl groups containing 16 and 18 carbon atoms. The composition and content thereof are as follows, calculated by the mass percentage of carbon atoms: Octadecanunsaturated alkyl containing 1 double bond 8% 4% octadecanoic unsaturated alkyl containing 2 double bonds Octadecanunsaturated alkyl containing 3 double bonds 83% Saturated alkyl containing 16 carbon atoms 4% 1% saturated alkyl containing 18 carbon atoms; The double bond position of the octadecanoic unsaturated alkyl group containing one double bond is between carbon atoms 9-10; The double bond positions of the octadecanoic unsaturated alkyl group containing two double bonds are respectively between the 9th-10th and 12th-13th carbon atoms; The octadecanoic alkyl group containing three double bonds is composed of an octadecanoic alkyl group whose double bond positions are between the 9th and 10th carbon atoms, the 12th and 13th carbon atoms, and an octadecanoic alkyl group whose double bond positions are between the 9th and 10th carbon atoms, the 11th and 12th carbon atoms, and the 13th and 14th carbon atoms; The mass ratio of the octadecanoic alkyl group having double bonds at the 9th to 10th, 12th to 13th, and 15th to 16th carbon atoms to the unsaturated alkyl group having double bonds at the 9th to 10th, 11th to 12th, and 13th to 14th carbon atoms is 3:80; For a better understanding, the composition of the mixed octadecanoic alkyl groups containing 1 double bond, 2 double bonds and 3 double bonds and the saturated alkyl groups containing 16 and 18 carbon atoms of R1 is summarized in the following table based on the mass percentage of carbon atoms:
[0034] X is O; R2 is a straight chain C3H6; M is N; R3 is a branched C9H 19 O3; R4 is a branched C6H 13 O2. Example 2
[0035] An emulsifier for SBS modified asphalt emulsification, its molecular structure is as follows: ; R1 in the molecular structure is the same as in Example 1; X is NH; R2 is a straight chain C3H6; M is N; R3 is a branched C6H 13 O2; R4 is hydrogen. Example 3
[0036] An emulsifier for SBS modified asphalt emulsification, its molecular structure is as follows: ; R1 in the above molecular structure is the same as in Example 1; X is NH; R2 is a straight chain C3H6; M is N; R3 is a branched chain C3H7O; R4 is a branched chain C3H7O.
[0037] The freezing point of the emulsifier used for SBS modified asphalt emulsification in the above Examples 1-3 was measured, and the appearance was observed at the same time. The results are shown in the following table:
[0038] It can be seen from the above table that the solidification point of the emulsifier used for SBS modified asphalt emulsification in the present application is 15-17°C, which shows that it can remain liquid at lower temperatures and can be used in environments with lower temperatures. Application Example 1
[0039] The use of an emulsifier for emulsification of SBS modified asphalt in Example 1 in preparing emulsified asphalt specifically comprises the following steps: (1) Calculated by mass percentage, the ratio of deionized water: 28% hydrochloric acid aqueous solution by volume percentage: an emulsifier for emulsifying SBS modified asphalt in Example 1: SBS modified asphalt is 39.4%: 0.3%: 0.3%: 60%. Prepare 394 g of deionized water, 3 g of 28% hydrochloric acid aqueous solution by volume percentage, 3 g of an emulsifier for emulsifying SBS modified asphalt in Example 1, and 600 g of SBS modified asphalt; (2) Heat deionized water to 55°C, add a 28% volume percent hydrochloric acid aqueous solution, control the speed to 80-100 r / min, and add an emulsifier for SBS modified asphalt emulsification at a rate of 5 g / min. Continue stirring after the addition is completed until a transparent homogeneous solution, i.e., soap solution, is formed. The temperature is controlled to 50-60°C and kept warm for later use; (3) Liquid asphalt preparation The temperature is controlled to be 140-150°C to heat the SBS modified asphalt until it becomes a flowing liquid with a viscosity of 10-1000cp to obtain liquid asphalt, and the temperature is continued to be controlled to be 140-150°C to keep it warm for standby use; The SBS modified asphalt is Shuanglong 70# SBS modified asphalt; (4) Preheating of colloid mill Rinse the colloid mill with 80-90℃ hot water and make the grinding head temperature reach 60-90℃, control the speed of the colloid mill to 2800-2900r / min, release all the hot water, and close the colloid mill and the outlet valve; (5) Add the soap solution obtained in step (2) to the preheated colloid mill at a rate of 800 g / min. After adding, start the colloid mill and control the rotation speed of the colloid mill to 2800-2900 r / min. Add the liquid asphalt obtained in step (3) to the soap solution in the colloid mill at a rate of 300 g / min. After adding, continue grinding for 1 min to obtain emulsified asphalt. Open the discharge valve to release the emulsified asphalt. Application Example 2
[0040] The use of an emulsifier for emulsification of SBS modified asphalt in Example 2 in preparing emulsified asphalt specifically comprises the following steps: The "emulsifier for emulsifying SBS modified asphalt in Example 1" in each step of Application Example 1 is replaced with "an emulsifier for emulsifying SBS modified asphalt in Example 2", and the rest is the same as Application Example 1 to obtain emulsified asphalt. Application Example 3
[0041] The use of an emulsifier for emulsification of SBS modified asphalt in Example 3 in preparing emulsified asphalt specifically comprises the following steps: The "emulsifier for emulsifying SBS modified asphalt in Example 1" in each step of Application Example 1 is replaced with "an emulsifier for emulsifying SBS modified asphalt in Example 3", and the rest is the same as Application Example 1 to obtain emulsified asphalt. Application Comparative Examples 1-3
[0042] The application of a liquid fast-cracking cationic polymer emulsifier for SBS modified asphalt emulsification in Example 1, Example 2 and Example 3 of Patent No. CN201811593163.X in preparing emulsified asphalt specifically includes the following steps: (1) Calculated by mass percentage, deionized water: 28% hydrochloric acid aqueous solution by volume percentage: prior art emulsifier: SBS modified asphalt is 39.4%: 0.3%: 0.3%: 60.0%. Prepare 394g of deionized water, 3g of 28% hydrochloric acid aqueous solution by volume percentage, 3g of prior art emulsifier and 600g of SBS modified asphalt; The emulsifiers of the prior art are respectively a liquid fast-cracking cationic polymer emulsifier for SBS modified asphalt emulsification obtained in Example 1, Example 2 and Example 3 of Patent No. CN201811593163.X; (2) Same as step (2) of application example 1; (3) Same as step (3) of application example 1; (4), same as step (4) of application example 1; (5) The same as step (5) of Example 1 is applied to obtain emulsified asphalt.
[0043] The residue on the sieve, the stability after standing for 1 day and 5 days, and the adhesion of the emulsified asphalt to the aggregate obtained by the above-mentioned application examples 1-3 (using the emulsified asphalt obtained by examples 1-3) and the application control example (using a liquid fast-cracking cationic polymer emulsifier for SBS modified asphalt emulsification obtained by examples 1, 2 and 3 of patent number CN201811593163.X) were measured, and the results are shown in the following table:
[0044] It can be seen from the above table that when the emulsifier dosage is 0.3% and the emulsification temperature is 140-150°C, the emulsification performance of the SBS modified asphalt is very good for the emulsification of the emulsifier for SBS modified asphalt of the special structure of the present application and the control example (CN201811593163.X liquid fast-cracking cationic polymer for SBS modified asphalt emulsification). The residual amount of SBS modified asphalt on the sieve in the final emulsified asphalt is 0; from the perspective of stability, the emulsifier for SBS modified asphalt emulsification of the special structure of the present application is better than the stability of the control example (CN201811593163.X liquid fast-cracking cationic polymer for SBS modified asphalt emulsification). The emulsified asphalt prepared by using the emulsifier for SBS modified asphalt emulsification in the application example of the present application is placed for 1 day, and the upper and lower concentrations do not change, and the stability is 0, while the control example using CN201811593163.X The emulsified asphalt prepared by the liquid fast-cracking cationic polymer for SBS modified asphalt emulsification in the present application has a difference of 0.1%-0.6% in upper and lower concentrations after being placed for 1 day, indicating that the emulsion in the control example has a slight stratification after being placed for 1 day. This situation is more serious after the emulsified asphalt is placed for 5 days. The emulsified asphalt prepared by the emulsifier for SBS modified asphalt emulsification with the special structure of the present application has a difference of 0.1%-0.2% in upper and lower concentrations after being placed for 5 days, while the control example uses CN201811593163.X The emulsified asphalt prepared by the liquid fast-cracking cationic polymer for SBS modified asphalt emulsification in the present application has a difference of 1.6%-3.4% in concentration after being placed for 5 days, that is, the emulsified asphalt prepared by the emulsifier for SBS modified asphalt emulsification with the special structure of the present application has higher stability, which is at least 14 times higher than the emulsified asphalt obtained in the above-mentioned control example; in terms of the adhesion of the emulsified asphalt to the aggregate, the emulsified asphalt prepared by the emulsifier for SBS modified asphalt emulsification with the special structure of Examples 1-3 of the present application has an adhesion of 100% to the aggregate, while the emulsified asphalt prepared by CN201811593163.X The adhesion of the emulsified asphalt prepared by the liquid fast-cracking cationic polymer for emulsification of SBS modified asphalt in Examples 1-3 to the aggregate is 95%, among which the adhesion of the emulsified asphalt prepared in Control Example 1 to the aggregate is 95%, which shows that the emulsified asphalt prepared by the emulsifier for emulsification of SBS modified asphalt with the special structure of the present application has better adhesion. Due to the better adhesion, it is also indirectly shown that the emulsified asphalt prepared by the emulsifier for emulsification of SBS modified asphalt with the special structure of the present application has better wear resistance, peeling resistance and waterproofness when paving the road surface, and the service life of the road will also be extended.
[0045] The peak particle size, average particle size, X90 particle size, color, and state of the emulsified asphalt after standing for 1 day of the emulsified asphalt obtained by using Examples 1-3 of the present application (using the emulsifier for emulsification of SBS modified asphalt obtained by Examples 1-3) and the control examples 1-3 (using the liquid fast-cracking cationic polymer emulsifier for emulsification of SBS modified asphalt disclosed in Examples 1-3 of CN201811593163.X) were measured or observed, and the results are shown in the following table:
[0046] Note: X90 means the average particle size of 90% of the particles; It can be seen from the above table that the particle size of the emulsified asphalt obtained by emulsifying SDS modified asphalt with the emulsifier for SBS modified asphalt emulsification obtained in Examples 1-3 of the present application is smaller, with an average particle size of 0.85-0.91µm, a peak particle size of 0.98-1.58µm, and an X90 average particle size of 0.92-1.15µm. The three are very close, indicating that the particle size distribution of the emulsified asphalt is uniform, which means that the emulsified asphalt has good stability. The light yellow-brown color of the emulsified asphalt can also be used to judge that the particle size of the emulsified asphalt is small, the particles are uniform, and it is not easy to stratify after being placed. This shows that the emulsifier for SBS modified asphalt emulsification in the examples of the present application has a good emulsification effect on SBS modified asphalt, high emulsion stability, a long storage period when used, and is easy to use.
[0047] The emulsified asphalt obtained by emulsifying SBS modified asphalt with the liquid fast-cracking cationic polymer for SBS modified asphalt emulsification used in Control Examples 1-3 has a slightly larger particle size, with an average particle size of 2.19-2.58µm, a peak particle size of 3.23-4.68µm, and an X90 average particle size of 4.43-6.37µm, that is, the particle size distribution is slightly wide, the color is slightly darker (brown), and there is a small amount of crusting on the surface after being placed for 1 day, which also shows that the liquid fast-cracking cationic polymer for SBS modified asphalt emulsification is not as effective as the emulsifier for SBS modified asphalt emulsification in the present application.
[0048] The emulsified asphalt obtained in the above-mentioned application examples 1-3 and the application control examples 1-3 were mixed with stones, and the obtained mixtures were used for the small slope heavy load road maintenance test sections, that is, the emulsified asphalt prepared in the application examples 1-3 and the application control examples 1-3 were used to pave 1 km sections, and the parameters such as the emulsified asphalt, stone type and gradation, oil-stone ratio and construction process technology used for paving were carried out in accordance with the industry standard JTG / TF40-02-2005. The road surface conditions after 3 months and half a year after paving are as follows: Three months after paving, the pavement paved with the mixture obtained by mixing the emulsified asphalt obtained by Example 1-3 and the control example 1-3 and stone had no potholes or cracks, but the pavement paved with the mixture obtained by mixing the emulsified asphalt and stone obtained by the control example 1-3 looked whiter than when it was just paved, indicating that the asphalt wrapped around the stone on the road surface fell off a little after being rolled over by vehicles, while the pavement paved by Example 1-3 had almost no change.
[0049] After half a year of paving, the color of the road surface paved with the mixture obtained by mixing the emulsified asphalt obtained in Examples 1-3 and stone did not change, and there was no stone falling off, empty grooves, cracks, etc., while the color of the road surface paved with the mixture obtained by mixing the emulsified asphalt obtained in Control Examples 1-3 and stone became white, and a small amount of stone fell off, but there were no obvious potholes and cracks.
[0050] The results of the above-mentioned paving experiments also indirectly indicate that after the road is paved with the emulsified asphalt of the present application (emulsified asphalt obtained by emulsifying SBS modified asphalt with the emulsifier for emulsifying SBS modified asphalt of the present application), the paved road surface has better wear resistance, peeling resistance and waterproofness, and the service life of the road will be relatively longer.
[0051] In summary, the emulsifier used for SBS modified asphalt emulsification in the present application has a strong emulsification ability for SBS modified asphalt, the resulting emulsified asphalt has better stability and adhesion to aggregates, the paved road surface has better wear resistance, anti-stripping and waterproof properties, and the road service life will be longer.
[0052] The above contents are only basic descriptions and preferred solutions of the present invention, and any equivalent changes made according to the technical solutions of the present invention shall fall within the protection scope of the present invention.
Claims
1. An emulsifier for emulsification of SBS modified asphalt, wherein the emulsifier for emulsification of SBS modified asphalt has a freezing point of 15-17° C. and a molecular structure as shown below: ; Features: The R1 is composed of mixed octadecanoic unsaturated alkyl groups containing 1 double bond, 2 double bonds and 3 double bonds and saturated alkyl groups containing 16 and 18 carbon atoms. Calculated by the mass percentage of carbon atoms, its composition and content are as follows: Octadecanunsaturated alkyl containing 1 double bond 8% 4% octadecanoic unsaturated alkyl containing 2 double bonds Octadecanunsaturated alkyl containing 3 double bonds 83% Saturated alkyl containing 16 carbon atoms 4% 1% saturated alkyl containing 18 carbon atoms; Among them, the double bond position of the octadecanoic unsaturated alkyl group containing one double bond is between the 9th and 10th carbon atoms; The double bond positions of the octadecanoic unsaturated alkyl group containing two double bonds are between the 9th-10th and 12th-13th carbon atoms, respectively; The octadecanoic alkyl group containing three double bonds is composed of an octadecanoic alkyl group whose double bond positions are between the 9th to 10th, 12th to 13th, and 15th to 16th carbon atoms and an octadecanoic alkyl group whose double bond positions are between the 9th to 10th, 11th to 12th, and 13th to 14th carbon atoms, respectively. The mass ratio of the octadecanoic alkyl group whose double bond positions are between the 9th to 10th, 12th to 13th, and 15th to 16th carbon atoms to the unsaturated alkyl group whose double bond positions are between the 9th to 10th, 11th to 12th, and 13th to 14th carbon atoms is 3:
80. The X is O or NH; R2 is a straight chain C3H6; M is N or NH; R3 is a branched C 3-9 H 7-19 O 1-3 ; R4 is hydrogen or branched C 3-6 H 7-13 O 1-2 ; The above R3 and R4 are the same or different.
2. An emulsifier for SBS modified asphalt emulsification according to claim 1, characterized in that In the molecular structure: The M is N; The branched chain C 3-9 H 7-19 O 1-3 For branched chain C9H 19 O3, branched C3H7O or branched C6H 13 O2; The branched chain C 3-6 H 7-13 O 1-2 It is branched C3H7O or branched C6H 13 O2.
3. An emulsifier for SBS modified asphalt emulsification according to claim 2, characterized in that In the molecular structure: Said X is O; M is N; R3 is a branched C9H 19 O3; R4 is a branched C6H 13 O2.
4. An emulsifier for SBS modified asphalt emulsification according to claim 2, characterized in that In the molecular structure: Said X is NH; M is N R3 is a branched C6H 13 O2; R4 is hydrogen.
5. An emulsifier for SBS modified asphalt emulsification according to claim 2, characterized in that In the molecular structure: Said X is NH; M is N; R3 is a branched chain C3H7O; R4 is a branched chain C3H7O.
6. Use of the emulsifier for SBS modified asphalt emulsification as claimed in any one of claims 1 to 5 in the emulsification of SBS modified asphalt.
7. The emulsifier for SBS modified asphalt emulsification according to claim 6 is used in SBS modified asphalt emulsification, characterized in that During the emulsification process, the amount of emulsifier used for SBS modified asphalt emulsification is based on a mass ratio of emulsifier used for SBS modified asphalt emulsification: SBS modified asphalt of 0.5:100, and the temperature is controlled at 140-150°C during the emulsification process.
8. The emulsified asphalt obtained by using the emulsifier for SBS modified asphalt emulsification according to claim 7 in SBS modified asphalt emulsification, characterized in that Calculated by mass ratio, the emulsifier used for SBS modified asphalt emulsification: emulsified asphalt is 0.3:100.
Citation Information
Patent Citations
Composition of cationic asphalt emulsifier, preparation method and application thereof
CN101845228B
Y-type liquid quick-cracking cationic emulsifier for SBS modified asphalt emulsifying and application thereof
CN109575313A